Grape seed extract improves intestinal barrier integrity and performance: Evidence from in vitro, Caenorhabditis elegans and Drosophila melanogaster experiments and a study with growing broilers. (April 2023) - Sandner, Georg; Stadlbauer, Verena; Sadova, Nadiia; Neuhauser, Cathrina; Schwarzinger, Bettina; Karlsberger, Lea; Hangweirer, Kerstin; Antensteiner, Katharina; Stallinger, Alexander; Aumiller, Tobias; Weghuber, Julian
Abstract: Grape seed extract (GSE) is an interesting source for polyphenols and other phytochemicals with high antioxidant potential. Here, we report on a comprehensive study investigating GSE in various in vitro and in vivo experiments. Obtained results indicate that GSE improves parameters related to intestinal barrier integrity in cell culture, C. elegans and D. melanogaster . Faster wound healing was observed in a scratch assay using intestinal IPEC-J2 cells when pre-treated with GSE. Furthermore, reactive oxygen species were found to be significantly decreased in cell culture and C. elegans experiments. In C. elegans, qPCR gene expression analysis revealed significant modulations after 24 h of GSE treatment. Finally, a 42-day broiler feeding study revealed a dose dependant effect on growth performance in the GSE supplemented groups. In conclusion, GSE was found to provide promising properties including wound closure, intestinal integrity, and antioxidant activity. Graphical abstract: Image 1 Highlights: Grape seed extract (GSE) provides faster wound-closure in IPEC-J2 intestinal cells. Oxidative stress was reduced upon grape seed treatment in Caco-2, IPEC-J2 and C. elegans . Intestinal integrity and lifespan was improved in C. elegans and D. melanogaster . Performance parameters improved in the first two weeks of broiler development.